Some T 2 Terrace Soils of Peninsular Malaysia: II. Mineralogy and Physico-chemical Characteristics* - Jusop, Shamsuddin; Tessens, Eddy (1985)
The amount of gibbsite in the clay fraction of T 2 terrace so£ls appears to increase with the increase of sand content and with the improvement of drainage conditions. Kaolinite is the main mineral £n the clay fraction of so£ls. The imperfectly and poorly drained ones may also contain some mica, chlorite, mixed layers and feldspar. Anatase accumulates in the silt fraction of the well rjrained soils. The dominance of 1:1 clay minerals and/or sesquioxides is reflected £n the£r physico-chemical properties. Apparent CEC decreases with a decrease £n silt/clay ration. WDC/clay % appears to decrease with an increase in A l and/or organic matter. The ratio also decreases as the pH approaches pHo'